The Influence of Schools’ level complexity on Literacy Development - Roca, Claudia; Sanz, Marta; Vílchez, Víctor; Cano, Cristina; Pujol, Aina; Benlloch, Cristina; Montore, Sara; Sáez, Laura; Camps, Anna; Andreu, Llorenç (Revista de Investigación en Logopedia, 2025)
School segregation, which involves the concentration of students from socioeconomically disadvantaged backgrounds in certain schools, is associated with lower literacy scores. The purpose of this study is to analyze the relationship between the level of complexity of educational centers and performance in various literacy skills in Catalonia. A total of 836 students from first to fourth grade in 29 schools in Catalonia participated in the study, 21 schools with high socioeconomic complexity and 8 with low complexity. All participants were assessed in reading and writing skills. In first and second grades, scores in all tests were significantly lower among students attending schools with high socioeconomic complexity. In third and fourth grades, these differences persisted in tests related to oral language, while in decoding-related skills, no significant differences between groups were observed. School segregation of students with high socioeconomic complexity is linked to lower reading and writing performance in the Catalan language compared to those enrolled in schools with lower complexity levels. These results highlight the inequalities present in schools based on socioeconomic complexity and emphasize the need for educational policies aimed at promoting greater equity in education.
Keywords: reading; writting; socioeconomic level; school segregation